The Relationship Between Self-Efficacy And The Occurrence Of Depression In Non-Hemorrhagic Post-Stroke Patients - Azano, Ningrum Sahiratul; Lahdji, Aisyah; Anggraheny, Hema Dewi (University of Muhammadiyah Semarang, 2024)
Stroke is a disease that can occur suddenly and is caused by blood vessel disorders and can cause death. According to the Health Service in 2017, the prevalence of non-hemorrhagic stroke in Central Java province was 64.7%. The impact of a stroke is psychological disorders including anxiety or stress and depression. Self-efficacy plays an important role in the level of post-stroke depression and it was also found that stroke sufferers with higher levels of self-efficacy had fewer depressive symptoms. The aim of this study was to determine the relationship between self-efficacy and the occurrence of depression in non-hemorrhagic post-stroke patients. This research is a descriptive-analytical study with a cross-sectional approach. The population in the study was 70 non-hemorrhagic post-stroke patients at KRMT Wongsonegoro Hospital, Semarang City using consecutive sampling techniques. Data collection uses a questionnaire. Relationship analysis used the Spearman rank test and t-test. The majority of respondents had a moderate level of self-efficacy as many as 42 respondents (60%) and did not experience depression as many as 36 respondents (51.4%). The results of the Spearman rank test showed a p-value of 0.000 and a positive correlation strength of 0.704, which means there is a relationship between self-efficacy and the incidence of depression in patients after non-hemorrhagic stroke. The higher the level of self-efficacy, the lower the incidence of depression in patients after non-hemorrhagic stroke.